Time based incremental backup scheme for mobile cloud computing - Yun-fei CI; Guo-zhen SHI; Rong-na XIE; Yao-ming PAN; Feng YANG; Si-shui YE (网络与信息安全学报)
A time-based data secure backup mechanism for moving the cloud was presented.Time was considered as a parameter into the data encryption for the important information in mobile device and backups the users' data ac-cording to the time period.It had not only solved the issue of the latest timely backup sensitive data,but also solved the entire ciphertext leak caused by missing the backup key.